2023
DOI: 10.1002/adbi.202200323
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Histone Modifications in Heat Signal Transduction in Plants

Abstract: Global warming and the more frequent occurrence of extremly high temperatures seriously affect crop yields. Heat stress (HS) has become a major environmental factor threatening food security worldwide. Understanding how plants sense and respond to HS is of clear interest to plant scientists and crop breeders. However, it is not trivial to elucidate the underlying signaling cascade, as specific cellular responses (ranging from detrimental to systemic effects) must be disentangled. Plants respond and adapt to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition to protein kinase-mediated phosphorylation, histone modifications play a crucial role in rapidly bridging heat signals to transcriptional programs (Han et al, 2022;Hou et al, 2022;Perrella et al, 2022;Bai et al, 2023). A recent study by Niu et al (2022) demonstrated that HISTONE DEACETYLASE 9 (HDA9) acts as a novel and evolutionarily conserved cytoplasmic thermosensor responsible for transmitting heat signals to the nucleus.…”
Section: Heat Perception and Signal Transduction In Cytoplasmmentioning
confidence: 99%
“…In addition to protein kinase-mediated phosphorylation, histone modifications play a crucial role in rapidly bridging heat signals to transcriptional programs (Han et al, 2022;Hou et al, 2022;Perrella et al, 2022;Bai et al, 2023). A recent study by Niu et al (2022) demonstrated that HISTONE DEACETYLASE 9 (HDA9) acts as a novel and evolutionarily conserved cytoplasmic thermosensor responsible for transmitting heat signals to the nucleus.…”
Section: Heat Perception and Signal Transduction In Cytoplasmmentioning
confidence: 99%
“…In addition to protein kinase-mediated phosphorylation, histone modifications play a crucial role in rapidly bridging heat signals to transcriptional programs ( Han et al., 2022 ; Hou et al., 2022 ; Perrella et al., 2022 ; Bai et al., 2023 ). A recent study by Niu et al.…”
Section: Heat Perception and Signal Transduction In Cytoplasmmentioning
confidence: 99%
“…In addition to protein kinase-mediated phosphorylation, histone modifications play a crucial role in rapidly bridging heat signals to transcriptional programs (Han et al, 2022;Hou et al, 2022;Perrella et al, 2022;Bai et al, 2023). A recent study by Niu et al (2022) demonstrated that HISTONE DEACETYLASE 9 (HDA9) acts as a novel and evolutionarily conserved cytoplasmic thermosensor responsible for transmitting heat signals to the nucleus.…”
Section: Heat Perception and Signal Transduction In Cytoplasmmentioning
confidence: 99%